TEACHING WRITING A DESCRIPTIVE TEXT TO SENIOR HIGH SCHOOL STUDENTS BY USING THE CSW GAME - Rizki Annisa; Muhd. Al-Hafizh (Universitas Negeri Padang, 2013)
This article describes how to teach writing a descriptive text about someone by using the CSW (Catch, Speak and Write) game for Senior High School students of the tenth grade. The CSW (Catch, speak, and Write) game is one of games that invites students to play while learning. The CSW game or Catch, Speak and Write game, is a game that uses picture and chocolate as the media. By using the CSW game, students will play while learning by answering a few questions through a picture with chocolate as a media that will be thrown and caught by the student before the student answer the questions. By using the CSW game in teaching and learning process, the teacher’s role is very important to make the students more active and enthusiastic in learning so that the students’ difficulties in writing will be easier with a comfortable atmosphere. Abstrak Artikel ini menjelaskan bagaimana cara mengajarkan menulis descriptive text tentang seseorang dengan menggunakan the CSW (Catch, Speak and Write) game untuk siswa SMA kelas X. The CSW (Catch, speak, and Write) game adalah salah satu permainan yang mengajak siswa bermain sambil belajar. The CSW game atau Catch, Speak and Write game, adalah suatu permainan yang menggunakan chocolate dan gambar sebagai media pendukung. Di dalam the CSW Game siswa akan bermain sambil belajar dengan menjawab beberapa pertanyaan melalui sebuah gambar yang didukung dengan media chocolate yang akan dilempar dan ditangkap siswa sebelum siswa tersebut menjawab pertanyaan. Di dalam Penggunaan the CSW game guru sangat berperan penting untuk membuat siswa lebih aktif dan bersemangat dalam belajar sehingga kesulitan siswa dalam menulis terasa lebih mudah dengan suasana yang lebih nyaman.